Highly polar non-glycerol containing lipids present in our mitochondrial membranes (Revista Española de Fisiología, 1977)
Aqueous 80% ethanol extracts from the outer mitochondrial membranes contained a series of compounds, insoluble in chloroform-methanol (2:1) and soluble in chloroform-methanol-water (10:10:3). These compounds contain fatty acids, amino acids and hexoses. Procedures are described for the extraction, purification and cromatographic separation of these compounds. Five of them have been partially characterised. Some structural data are given. It is suggested that some relationship could exist with the glycosylation of the outer membrane proteins.